Multiuser untrusted relay networks with joint cooperative jamming and opportunistic scheduling under perfect and outdated CSI. Issue 23 (1st November 2016) - Ding, Fan; Wang, Hui; Zhang, Shengli; Dai, Mingjun
Abstract : A joint cooperative jamming and opportunistic scheduling (CJOS) scheme is proposed for a downlink multiuser relay network (MRN) with an untrusted fixed‐gain amplify‐and‐forward relay. Specifically, the source's confident message is protected by employing CJ at the destinations and multiuser diversity is harvested via OS. Unified tight approximation and asymptotic expressions for the system secrecy outage probability with perfect/outdated channel state information (CSI) are derived. Our results explicitly show that with perfect CSI, CJOS scheme can improve the secrecy diversity order from 1/2 in single‐user networks up to full diversity of 1 in MRNs. However, the outdated CSI degrades the secrecy diversity order from 1 to 1/2.